Endothelial glycocalyx degradation and disease severity in Plasmodium vivax and Plasmodium knowlesi malaria - Barber, Bridget E. (2021)
Degradation of the endothelial glycocalyx is associated with mortality in adult falciparum malaria. However, its role in the pathogenesis of non-falciparum malaria is unknown. In Malaysian patients with knowlesi (n = 200) and vivax (n = 61) malaria, and in healthy controls (n = 50), we measured glycocalyx breakdown products plasma syndecan-1 and urinary glycosaminoglycans, and evaluated correlations with biomarkers of disease severity. Urinary glycosaminoglycans were increased in patients with knowlesi and vivax malaria compared to healthy controls, and in knowlesi malaria were highest in those with severe disease. In knowlesi malaria, plasma syndecan-1 was also highest in those with severe disease, and correlated with markers of endothelial activation (angiopoietin-2, osteoprotegerin, ICAM-1), asymmetric dimethylarginine (ADMA) and impaired microvascular reactivity. Syndecan-1 also correlated with endothelial activation (ICAM-1, angiopoietin-2) and ADMA in vivax malaria. In knowlesi malaria increased syndecan-1 was associated with acute kidney injury, after controlling for age and parasitemia. In knowlesi malaria, the difference in median syndecan-1 between severe and non-severe disease was more marked in females than males. Endothelial glycocalyx degradation is increased in knowlesi and vivax malaria, and associated with disease severity and acute kidney injury in knowlesi malaria. Agents that inhibit glycocalyx breakdown may represent adjunctive therapeutics for severe non-falciparum malaria.